ANALISIS WACANA KRITIS (AWK) PENDEKATAN TEUN A. VAN DIJK TERHADAP BERITA ONLINE TVONENEWS.COM PEMBERITAAN KASUS GRATIFIKASI DAN TPPU ADHI PRAMONO BELUM DIPECAT DARI PNS DI KEMENKEU - Trisna Maolianti Sari; Agus Hamdani (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2024)
This research examines the case of gratification involving Adhi Pramono, which is currently a hot topic of discussion in Indonesia. This phenomenon raises concerns among the public, especially because the act of gratification occurred within the Ministry of Finance, potentially damaging the public's trust in government officials. This qualitative study utilizes data from the TVONENEWS.com portal, employing data collection techniques through documentation, observation, and direct note-taking in online mass media. The analysis of research data encompasses data editing, data presentation, and conclusions drawn using Teun A. van Dijk's discourse analysis model, which includes macrostructure, superstructure, and microstructure. The news analyzed is sourced from the portals Tribunnews.com, Detik.com, and Kompas.com. The results of critical discourse analysis indicate that the information presented in the news has met the critical analysis criteria of Teun A. van Dijk's model, covering text structure, social cognition, and social context. This research has implications for moral values, urging readers to be more selective in choosing news portals. Furthermore, the study encourages the public to be vigilant against any criminal activities, even in seemingly secure places. These conclusions can contribute to strengthening public understanding of the importance of vigilance and caution in consuming information and upholding moral values. Keywords: Critical Discourse Analysis, Teun A. Van Dijk, News